Chemometric classification of new Olea europaea L. cultivars developed through a crossbreeding program in Tunisia - Guellaoui, I.; M. Ayadi, F. Ben Amar; Boubaker, M. (Journal of Scientific Agriculture, 2019)
Five new olive (Olea europaea L.) cultivars issued from a Tunisian breeding program were released in 2017. This program aimed to improve the oil quality of the local cultivar ‘Chemlali Sfax’ which had mainly low oleic acid content. A wide genetic diversity was observed within the new cultivars which differ from the typical cultivar. The results of the morphological evaluation of the leaf, fruit and stone showed mainly a significant increase of the fruit size (medium) and the appearance of new morphological states for the fruit and the stone.